TARGETING THE POOR AND HUNGRY WITH POTATO SCIENCE - Thiele, G; Theisen, K; Bonierbale, M; walker, T (Potato Journal, 2013)
An updated targeting analysis for potato based on its local importance and a composite indicator of livelihood has been presented. in some areas, the potato crop is essential to the livelihood of a large number of people, elsewhere it is less essential, but still very important for subsistence and income generation. potato production grew faster than expected over the past fifteen years in all regions of developing countries except Latin america and east asia outside china. potato contributes in two different ways to the livelihoods of the poor. in some areas potato is a staple grown and eaten by the poor where it contributes directly to hunger reduction. elsewhere potato is a high value crop which contributes principally to poverty reduction by increasing income or creating employment. The evidence from income elasticities and higher than expected growth rates suggests that potato already is a pathway out of poverty for many farmers as a high value crop. The best way to reach the poor is to ensure that new varieties are intrinsically pro-poor. Much existing international agriculture research already includes pro-poor traits, such as yield stability, late blight and virus resistances. attention should be given to micro-nutrient availability and resistance to heat and drought as pro-poor traits.